Quality Framework And Indicators For Accreditation Of Teacher Education: International Cases And Suggestions For Nigeria - Nwokeocha, Steve (Advances in Social Sciences Research Journal, 2019)
This paper focused on teacher education and quality assurance issues particularly the quality framework and indicators for accrediting teacher education. It analysed the fact that all parts of the world have not shown equal commitment to the accreditation of teacher education. Similarly, what constitute quality framework and indicators for accrediting teacher education had varied among the countries, higher education agencies and teaching regulatory authorities. For Nigeria, though the professionalisation of teaching has advanced, the professional accreditation of teacher education has not kept pace with the advancement. This study was therefore undertaken to take stock of the international best practices in accreditation of teacher education with a view to suggesting quality framework and indicators for the professional accreditation of teacher education in Nigeria.